Yuri Borko – a Founder of European Integration Studies in Russia - O.V. Butorina (Современная Европа)
Regional integration studies constitute a relatively young area of academic knowledge since regional integration emerged as a new phenomenon in international relations after the Second World War. Professor Yuri Antonovich Borko who is turning 95 in February 2024, is an influential scholar and one of the founders of the Soviet and Russian school of European studies. This article aims to reveal his role in gaining and disseminating of new knowledge about regional integration processes. To do this, the author first traces the main milestones of Professor Borko’s academic path. Then the most important contributions to the literature (based on the criteria of novelty, valuable insight and confirmed forecasts) are pointed out in their interconnection with the international academic advance in the relevant areas of research. Finally, the key achievements of professor Borko in spreading knowledge, graduate and postgraduate teaching are assessed, shedding light on the innovative educational methods employed and illustrating his distinct personality profile. The findings suggest that the most valuable results of professor’s Borko research relate to the areas of the EU social policy, the evolution of the European idea, the interrelation between deepening and widening in the integration process. His reasoning about universal and specific features of the EU experience proves seminal for the national research community. A number of publishing projects and networking activities within the Association of European Studies initiated by professor Borko notably facilitated the establishment of research schools in international relations in Russian regions.